Dual RNA-Seq Unveils Pseudomonas plecoglossicida htpG Gene Functions During Host-Pathogen Interactions With Epinephelus coioides - Huang, Lixing; Zhao, Lingmin; Liu, Wenjia; Xu, Xiaojin; Su, Yongquan; Qin, Yingxue; Yan, Qingpi (Frontiers in Immunology, 2019)
Pseudomonas plecoglossicida is a temperature-dependent facultative pathogen that is associated with diseases of multiple fish, mainly at 15-20 °C. Expression of P. plecoglossicida htpG gene was found significantly up-regulated at virulent (18 °C) temperature than at avirulent (28°C) temperature, which was verified by quantitative real-time PCR (qRT-PCR). Expression of htpG was highly consistent with the processing of white nodules disease caused by P. plecoglossicida, which reached the peak at 48h. RNAi significantly reduced the content of htpG mRNA of P. plecoglossicida, while the growth was not significantly affected. The infection of htpG-RNAi strain resulted in the onset time delay, 45% reduction in mortality of Epinephelus coioides, alleviates in the symptoms of E. coioides spleen, and decreased distribution in host organs. After htpG was silenced, through dual RNA-seq we found that various virulence cluster genes of P. plecoglossicida closely related to the ability to form biofilms, move and the formation of ribosomes was reduced, while LexA was predicted to be the common transcription factor for these cluster genes. These indicated that htpG might play a key role through regulating LexA and then other genes in the pathogenic process of P. plecoglossicida. Compared with wild-type strain infected fish spleen, genes expression in htpG-RNAi strain infected fish spleen was significantly changed. From this, we deduced the htpG-dependent virulent mechanism, htpG-dependent defense mechanism, and htpG-independent defense mechanism. By constructing the pathogen-host integration network, we could found that infection induce the expression of host genes related to immune response, while infection reduce the expression of bacterial virulence genes. Close integration was found between host immune genes and bacterial virulence genes, while IL6, IL1R2, IL1B and TLR5 played key role in the network. Further analysis with GeneMANIA indicated that flgD and rplF might play key role during the htpG-dependent virulence regulation, which was accordance with the reduced biofilm production, motibility and virulence in htpG-RNAi strain. Meanwhile, IL6 and IL1B was found to play key role during the defense of P. plecoglossicida, while CELA2, TRY, CPA1, CPA2 and CPB1 were important targets for P. plecoglossicida to attack host.